Educação infantil e participação: um estudo das representações sociais de pais de uma escola pública municipal de Belém - FERREIRA, Heloiza do Socorro Nóbrega (Universidade Federal do Pará, 2011)
Made available in DSpace on 2011-03-23T21:19:32Z (GMT). No. of bitstreams: 0 === Item created via OAI harvest from source: http://www.bdtd.ufpa.br/tde_oai/oai2.php on 2011-03-23T21:19:32Z (GMT). Item's OAI Record identifier: oai:bdtd.ufpa.br:226 === This work deals with the Social Representations and Infantile Education. It analyzes the parents' social Representations about their Infantile Education and participation in the Education of the children who study at public schools in the Belém's municipal net. It was based on the theoreticalmethodological referential of the Social Representations with bases on Moscovici (1978, 2003), Lefevre (2005), Jodelet (2001) and theoricists who study the childhood, infantile education and participation, such as Ariès (1981), Kramer (1984, 2003), Kuhlmann (2004), Sarmento (2001), Paro (2000), Lima (2008). The study is a research of the descriptive type. It had as instrument of data collection, questionnaires, images and focal group, in which participated mothers, grandmother and father (totaling twelve subjects), who had their children in the infantile education of a school of the municipal public net in the year of 2007. The results of the study reveal that the parents possess information about the Infantile Education with emphasis in the learning process and socialization. They believe that the infantile education will subsidize the success for the whole education of the children and consequently a professional future. The parents' social representations about their participation in the children's education are materialized in attendances to school meetings, orientation towards the school guidances and the dialogue with the professionals. In such a process of representations of participation, conducts of sharing are anchored for some, and for other parents, of listening, silence, reservedly shared to question the work developed by the school, having in mind that parents cultivate faiths and idealizations due to the school education and the authority that they realize in the professionals who educate their children. The dialogue with the parents demonstrated that this relationship is not free of conflicts or dissatisfactions. In our final considerations, elements that can contribute to the promotion of the parents' participation in the Infantile Education are pointed out. === Este estudo trata das Representações Sociais e Educação Infantil. Analisa as Representações sociais de pais sobre a Educação Infantil e sobre sua participação na educação dos filhos que estudam em escola pública na rede municipal de Belém. Fundamentou-se no referencial teórico-metodológico das Representações Sociais com base em Moscovici (1978, 2003), Lefevre (2005), Jodelet (2001) e teóricos que estudam a infância, educação infantil e participação, como Ariès (1981), Kramer (1984, 2003), Kuhlmann (2004), Sarmento (2001), Paro (2000), Lima (2008). O estudo é uma pesquisa do tipo descritiva. Teve como instrumento de coleta de dados questionários, imagens e grupo focal, dos quais participaram mães, avó e pai (totalizando doze sujeitos) que tiveram seus filhos na educação infantil de uma escola da rede pública municipal no ano de 2007. Os resultados do estudo revelam que os pais possuem informações sobre a Educação Infantil com ênfase no processo de aprendizagem e socialização, crêem que a educação infantil subsidiará o êxito por toda a escolarização dos filhos e conseqüentemente um futuro profissional. As representações sociais dos pais sobre sua participação na educação dos filhos, materializam-se mediante idas às reuniões escolares, orientação diante dos encaminhamentos da escola e o diálogo com os profissionais. Em tal processo de representações de participação ancoram-se condutas de partilhas para uns, e para outros pais, de escuta, silêncio, compartilhadas com reservas para questionar o trabalho desenvolvido pela escola, tendo em vista que os pais cultivam crenças e idealizações diante da educação escolar e da autoridade que reconhecem nos profissionais que educam seus filhos. O diálogo com os pais demonstrou que esta relação não está isenta de conflitos ou insatisfações. Em nossas aproximações conclusivas, apontamos elementos que possam contribuir com a promoção da participação dos pais na Educação Infantil.